Pelatihan Desain Grafis Menggunakan Canva untuk Meningkatkan Kapasitas Promosi Digital Desa Wisata Jamu Kiringan - Bashir, Nur Azmi Ainul; Hilmiawan, Gigih Aulia; Hernawan, Septian Rico (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
This community service activity aims to enhance the digital graphic design skills of the residents of Jamu Kiringan Tourism Village to promote local potential based on cultural identity. The main issues faced include limited digital media utilization and a lack of skills in creating visual promotional content, resulting in conventional and less engaging promotion. The community service was carried out using the Participatory Community-Based Training method combined with service-learning, consisting of four main stages: preparation and coordination, Canva training, mentoring and creative discussions, and evaluation and presentation of results. A total of 26 participants attended the three-day training, learning design principles, Canva usage, and practicing design creation with local themes. The results showed a significant improvement in technical skills, creativity, and participants’ understanding of visual branding strategies. The participants’ designs highlighted traditional village themes, such as herbal drinks and local atmosphere, and became adaptable digital promotional media across various platforms. This activity not only addressed the urgent need for digital promotion in the village but also motivated intergenerational collaboration and opened up sustainable creative economy opportunities for the village.